Range of motion as an outcome measure for knee osteoarthritis interventions in clinical trials: an integrated review. (22nd December 2020) - Epskamp, Samantha; Dibley, Hayley; Ray, Elizabeth; Bond, Nicole; White, Joshua; Wilkinson, Amanda; Chapple, Cathy M.
Abstract: Background: Osteoarthritis (OA) is a progressive disease causing pain and reduced range of motion (ROM), decreasing function and activity participation. Physiotherapy interventions improve symptoms and quality of life. Goniometry is one method for measuring ROM. Objective: To conduct an integrative review investigating use of ROM for participants with knee OA following physiotherapy interventions in clinical trials, including reliability, validity and responsiveness of goniometry for measuring knee ROM. Major Findings: Forty-two articles fulfilled the inclusion criteria. Twenty-six studies used OA patient-reported outcome measures in addition to ROM. Twenty-eight studies reported their own psychometric data, with generally excellent inter- and intra-rater reliability. Nine reported good to excellent criterion validity. Four studies reported limited and variable data on responsiveness. Conclusions: Knee ROM is commonly used as an outcome measure in clinical trials of people with knee OA. Goniometry is a reliable and valid way to measure knee ROM, and is a convenient, accessible outcome measure for clinical trials and physiotherapy practice. We suggest combining patient-reported outcome measures with goniometry may provide a more holistic view of the person's wellbeing, function, and participation. Further research is needed to gain a broader understanding of the validity, and responsiveness specifically for people with knee OA.